Literature Review: The Effect of Mindfulness Therapy on Reducing Anxiety Levels in The Elderly - Alfira Rahma Dhani; Agus Sudaryanto (GLOBAL HEALTH SCIENCE GROUP, 2024)
Anxiety. one of the nursing therapies that can be used to reduce anxiety in the elderly is mindfulness therapy. mindfulness is an intervention practice that largely focuses on non-judgmental awareness of current conditions. objective: to determine the effectiveness of mindfulness therapy in reducing anxiety levels in the elderly. method: the research method used in this research is a literature review. each stage of study selection carried out by researchers uses the prisma flow diagram. results: based on the literature review that has been carried out, all types of mindfulness therapy interventions are considered to be able to reduce anxiety levels in the elderly. conclusion: anxiety problems are one of the problems experienced by the elderly. a mindfulness therapy intervention is considered to be able to reduce anxiety levels in the elderly.